Technology Acceptance Model for Examining the Feasibility of a Computer-based Test System (an Indonesian Context) - Nugroho, Septian; Budiyanto, Cucuk; Budianto, Aris (IJIE (Indonesian Journal of Informatics Education), 2018)
Indonesia is a country with rapid technological developments in all sectors including education. This can be proved by the government's success in applying computer-based test in 2014 junior high school. Many conveniences obtained when the exam using computer such as the assessment automatically, get feedback quickly and the question can be stored in the bank question. In this research, computer-based test system will be developed based on the convenience as above and will be added some other features to suit of the school using waterfall development model. Additional features include classroom major, question grouping in the question bank, user management and ease of registration during new year academic calendar. After developing system has been done, the CBT system is tested to one class at a vocational high school in Indonesia using an system feasibility instrument adapted from technology acceptance model (TAM) to know the level of feasibility the CBT system in perceived usefulness and perceived easy of use. The test results show that CBT system is very suitable for use in the class and can be applied to all schools in Indonesia.